Malignant epignathus - Harijan Hanumantha Rayudu; Kilashnath Reddy; Kasa Lakshmi; Santhosh Varma (Wolters Kluwer Medknow Publications, 2011)
Report of a neonate with a huge mass protruding from the oral cavity. The mass has originated from the base of the tongue. Successful excision and histopathological examination revealed it to be a malignant epignathus.